48 hours to kill : a thriller - Bourelle, Andrew (Crooked Lane, 2021)
"Serving a ten-year sentence in a Nevada prison for armed robbery, Ethan Lockhart hopes that he can one day become a productive, law-abiding member of society ... When he's given a forty-eight-hour furlough to attend his sister Abby's funeral, he learns that her body was never found ... and he begins to suspect that there's more to her death than was reported ... But to get to the bottom of the mystery, he'll have to return to his unsavory past"--